Circulating miRNA-21 is an innovative biomarker for cardiovascular events in erectile dysfunction patients - Agulló, Laura; Segura, Ana; Ortuño-Miquel, Samanta; Brinca, Ana Teresa; Micol-Ponce, Rosa; Arrarte, Vicente; Ponce, María Rosa; Miró-Martínez, Pau; Zandonai, Thomas; Peiró, Ana M. (Frontiers in Cardiovascular Medicine, 2024)
Introduction It is well-known that circulating microRNAs (miRNAs) play a relevant role in many kinds of diseases by regulating the expression of genes involved in various pathophysiologic processes, including erectile dysfunction (ED) and cardiovascular diseases (CVD). Purpose This study aimed to identify the miRNA-21 profile in the blood samples of patients with ED, CVD, and the combination of both pathologies to elucidate the potential function of miRNA-21. Methods A total of 45 patients with CVD and/or who underwent the erectile function test were included and divided into the following categories: CVD with ED (cases, n = 29) and controls (n = 16) with either ED or CVD. Real-time polymerase chain reaction analysis verified the results. miRNA-21 expression was quantified, and informatics analysis was applied to predict the functions of this differentially expressed miRNA-21. Results A total of 64% of cases (63 ± 9 years, 66% with severe ED, 56% with CV ejection fraction) first presented ED as the sentinel clinical manifestation. Serum miRNA-21 levels in the control ED were significant, up to 10-fold higher than in the CVD controls and cases. A significant inverse (p = 0.0368, β = −2.046) correlation was found between erectile function and miRNA-21 levels. Conclusions Our study provides comprehensive insights into the functional interaction between miRNA-21 and ED in CVD patients. Its relevance lies in the potential of miRNA as a biomarker to be applied in the cardiovascular predictive medicine field.